Surrogate endpoints for overall survival in randomized clinical trials testing immune checkpoint inhibitors: a systematic review and meta-analysis - Sala, Isabella; Pagan, Eleonora; Pala, Laura; Oriecuia, Chiara; Musca, Marco; Specchia, Claudia; De Pas, Tommaso; Cortes, Javier; Giaccone, Giuseppe; Postow, Michael; Gelber, Richard D.; Bagnardi, Vincenzo; et al. (Frontiers in Immunology, 2024)
There is debate on which are the best surrogate endpoint and metric to capture treatment effect on overall survival (OS) in RCTs testing immune-checkpoint inhibitors (ICIs).We systematically searched for RCTs testing ICIs in patients with advanced solid tumors. Inclusion criteria were: RCTs i) assessing PD-(L)1 and CTLA-4 inhibitors either as monotherapy or in combination with another ICI, and/or targeted therapy, and/or chemotherapy, in patients with advanced solid tumors; ii) randomizing at least 100 patients.We performed a meta-analysis of RCTs to compare the surrogacy value of PFS and modified-PFS (mPFS) for OS in RCTs testing ICIs, when the treatment effect is measured by the hazard ratio (HR) for OS, and by the HR and the ratio of restricted mean survival time(rRMST) for PFS and mPFS.61 RCTs (67 treatment comparisons and 36,034 patients) were included in the analysis.In comparisons testing ICI plus chemotherapy, HRPFS and HRmPFS both had a strong surrogacy value (R 2 =0.74 and R 2 =0.81, respectively). In comparisons testing ICI as monotherapy, HRPFS was the best surrogate, although having a moderate correlation (R 2 =0.58). In comparisons testing ICI plus other treatment(s), the associations were very weak for all the surrogate endpoints and treatment effect measures, with R 2 ranging from 0.01 to 0.22.In RCTs testing ICIs, the value of potential surrogates for HROS was strongly affected by the type of treatment(s) tested. The evidence available supports HRPFS as the best surrogate, and disproves the use of alternative endpoints, such as the mPFS, or treatment effect measures, such as the RMST